Beyond Civil Society : Activism, Participation, and Protest in Latin America - Escobar, Arturo, 1951-; Laó-Montes, Agustín; Baiocchi, Gianpaolo, 1971-; Thayer, Millie; Rubin, Jeffrey W.; Alvarez, Sonia E., 1956- (Book collections on Project MUSE., 2017)
Beyond Civil Society challenges current understandings of the politics of protest, activism, and participation by examining the ways in which social movements in late twentieth- and early twenty-first-century Latin America blur the boundaries between civil and uncivil activism and between activism carried out in state and the streets.